Renewable Sources of Plant Biostimulation: Microalgae as a Sustainable Means to Improve Crop Performance - Chiaiese, Pasquale; Corrado, Giandomenico; Colla, Giuseppe; Kyriacou, Marios C.; Rouphael, Youssef (Frontiers in Plant Science, 2018)
Plant biostimulants (PBs) attract interest in modern agriculture as a tool to enhance crop performance, resilience to environmental stress, and nutrient use efficiency. PBs encompass diverse organic and inorganic substances ((humic acids and protein) hydrolysates as well as prokaryotes (e.g. plant growth promoting bacteria) and eukaryotes such as mycorrhiza and macroalgae (seaweed). Microalgae are receiving growing interest from scientists, extension specialists, private industry and plant growers because their simple unicellular structure, high photosynthetic efficiency and the ability to grow in heterotrophic conditions, adaptability to domestic and industrial wastewater, amenability to metabolic engineering and possibility to yield valuable co-products. On the other hand, large-scale biomass production and harvesting still represent a bottleneck for some applications. Although it is long known that microalgae produce several complex macromolecules that are active on higher plants, their targeted applications in crop science is still in its infancy. This paper presents an overview on main extraction methods from microalgae, their bioactive compounds, and application methods in agriculture. Mechanisms of biostimulation that influence plant performance, physiology, resilience to abiotic stress as well as the plant microbiome are also outlined. Considering current state-of-the-art, perspectives for future research on microalgae-based biostimulants are discussed, ranging from the development of crop-tailored, highly effective products to their application for increasing sustainability in agriculture.